Africa’s Trade in Services and Economic Partnership Agreements - World Bank (World Bank, 2012)
Trade can play a crucial role in the development of services sectors in Africa. Services offer new dynamic opportunities for exports, especially for land-locked countries, while opening up to imports of services and foreign direct investment is a key mechanism to increase competition and drive greater efficiency in the provision of services in the domestic economy. Lower prices, higher quality and wider access to services raises productivity improves competitiveness and is critical for poverty reduction. But trade opening may need to be coordinated with regulatory reforms, to ensure efficient outcomes, while additional policies may be required to ensure that public policy objectives regarding equity are achieved. This places emphasis on the capacity to define and implement sound regulatory policies for services sectors, capacity that is limited in many African countries. Regulatory and trade reforms in Africa need to be supported with technical and financial assistance. Such assistance should be available to all African countries that wish to reform their services sectors, whether they negotiate and sign an Economic Partnership Agreement (EPA) or not. An independently managed fund for services trade reform in Africa, organized around common priority sectors, that would allocate resources to support implementation of reforms and consultants according to expertise, not nationality, will be the most appropriate vehicle for providing technical assistance and building capacity.